2023
DOI: 10.3390/ph16040477
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin Enhanced Carbapenem Activity with Improved Antibacterial Effects and Eradicates Established Acinetobacter baumannii Biofilms

Abstract: Biofilm-mediated infections are critical to public health and a leading cause of resistance among pathogens, amounting to a prolonged hospital stay and increased mortality rate in the intensive care unit. In this study, the antibacterial and antibiofilm activities of rifampicin or carbapenem monotherapies were compared with rifampicin and carbapenem combination therapies against rifampicin-resistant and carbapenem-resistant Acinetobacter baumannii isolates. Among 29 CRAB isolates, 24/29 (83%) were resistant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…These findings can be explained by considering a previous in vitro study that found serum resistance by biofilm formation against complement activity of the human immune system 23 . Additionally, whole genome sequencing analysis showed the presence of the genes responsible for biofilm formation, serum resistance, other virulence‐associated genes, and various antimicrobial resistance genes among A. baumannii isolates causing bacteremia or pneumonia 17,24,25 …”
Section: Discussionmentioning
confidence: 86%
“…These findings can be explained by considering a previous in vitro study that found serum resistance by biofilm formation against complement activity of the human immune system 23 . Additionally, whole genome sequencing analysis showed the presence of the genes responsible for biofilm formation, serum resistance, other virulence‐associated genes, and various antimicrobial resistance genes among A. baumannii isolates causing bacteremia or pneumonia 17,24,25 …”
Section: Discussionmentioning
confidence: 86%